2014
DOI: 10.1158/1541-7786.mcr-13-0418
|View full text |Cite
|
Sign up to set email alerts
|

KIF3a Promotes Proliferation and Invasion via Wnt Signaling in Advanced Prostate Cancer

Abstract: Aberrant activation of the Wnt/β-catenin signaling pathway is a critical event in advanced prostate cancer, but the genetic alterations which activate the Wnt signaling pathway in many other cancers are rarely observed in prostate cancer. Other molecular mechanisms that regulate the Wnt signaling pathway in prostate cancer remain to be identified. Here it is demonstrated that KIF3a, a subunit of kinesin-II motor protein, functions as an agonist of the Wnt signaling pathway in prostate cancer. KIF3a is up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 42 publications
3
47
0
1
Order By: Relevance
“…When fibroblasts differentiate into myofibroblast, the ability of synthesis ECM is enhanced and fibrosis proceeding is aggravated [36]. The importance of Wnt signaling in metastatic and invasive capacity is already demonstrated in many tumor cells [37,38]. Therefore, we used scarification essay and found that NSC668036 can remarkably depress the migration ability of fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…When fibroblasts differentiate into myofibroblast, the ability of synthesis ECM is enhanced and fibrosis proceeding is aggravated [36]. The importance of Wnt signaling in metastatic and invasive capacity is already demonstrated in many tumor cells [37,38]. Therefore, we used scarification essay and found that NSC668036 can remarkably depress the migration ability of fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…Bidwell et al (37) demonstrated that targeted c-Myc inhibitory polypeptides significantly suppressed breast cancer tumor growth in an orthotopic mouse model of breast cancer. Liu et al (38) identified that klf3a, a subunit of the kinesin-II motor protein, promotes cell proliferation and invasion via Wnt signaling in advanced prostate cancer, modulating cyclin D1 and c-Myc expression. It has been reported that the excessive production of MMP9, the major MMP, is associated with the metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thakur et al demonstrated that TGF-β upregulates the expression of Snail1 and increases the motility and invasiveness of human prostate cancer cells by activating the TRAF6/p38MAPK pathway (46). Apart from TGF-β signaling, other signal pathways including PI3K/AKT (47), NF-κB (48,49), Hedgehog (50), MAPK/ERK (51), p38MAPK (52) and Wnt/β-catenin (53,54) play important roles in tumor progression (Fig. 2).…”
Section: Signal Transduction In Tumor Invasion and Metastasismentioning
confidence: 99%